Employee engagement in 5-star and 3-star hotel chains of Jaipur: A comparative study - Sugandha Sharma (Mathematical Statistician and Engineering Applications, 2022)
The term "employee engagement" describes a worker’s dedication to the organization’s values and his enthusiasm for the tasks assigned. Engaging employees is a shared responsibility between engagement and staff. The purpose of this study is to examine the differences between employee engagement initiatives at 5-star and 3-star Jaipur hotel chains. The researchers were moved to investigate the hotel sector by the pressing question of where best to prioritise human resource initiatives like employee engagement. The need to educate people more on the advantages of service providing that flow from a fully invested staff was a major worry. Work Environment, Leadership, Co-worker Relationship, T&D facility, Compensation, Organizational Policy, and Workplace well-being are the six dimensions of employee engagement on which this analysis was based. The descriptive nature of the study indicates that it is primarily qualitative. Two hundred workers (hundred from 3 star hotel chains & 100 from 5 star hotel chains) were given a structured questionnaire on the factors that influence employee engagement, and the results were analysed using the SPSS software. Finings revealed 5-star hotels are better placed in terms of employee engagement as compared to 3-star hotels. It is recommended that 3-star hotels.